A cooperação design de games e neurociência como estratégia à superação do cybersickness - MORENO, Felipe Servilha (2018)
The technological evolution of HMDs is responsible for making devices available that are lighter, cheaper and more operational, as well as being aware of the risks of cybersicness. Cybersickness involves a range of symptoms similar to those of motion sickness, which affects a significant number of users and is currently regarded as one of the main obstacles to virtual reality helmets in the market. The focal point of this dissertation is on merging the fields of knowledge of Neuroscience and Games Design as a strategy for mitigating the symptoms of cybersickness. It sets out the results obtained from an experiment carried out with two groups of volunteers – heavy and low users of games for HMDs. These results underpin the sensory rearrangement theory and point out the kind of design choices that can trigger the symptoms of cybersickness. As a result, it is becoming possible to design games by predicting the design decisions required to overcome the problem of this malady.